Economies of the Wor(l)d: Reading Derrida's White Mythology: Metaphor in the Text of Philosophy - Babiak, Peter Roman (My University, 1990)
Most deconstructive and Marxist cultural theories are at odds with one another because they are concerned with two very different subjects or entities: words and the world. In what follows I will try to show that these two potent theories are fundamentally at odds with each other because they reside on opposite sides of some formative binary oppositions, such as abstract/ concrete, ide81/material, sensible/intelligible, physical/spiritual, and signifier/signified. Of course each of these oppositions is a metaphor; as such the relationship between Marxism and deconstruction must therefore proceed from and always refer back to this metaphorical condition. It is in my political interest to incorporate within this figurative type of atavism the concepts of economy, exchange, labour, power, property, and ideology, the very concepts in which we find not the opposition between Marxism and deconstruction but their relative sameness. Since Jacques Derrida is often referred to as the foremost deconstructive theorist, and since so much of his work is concerned with the theory of language (and metaphor), I will attempt to deliver my co-articulation of Marxism and deconstruction to a political and (I hesitate only minimally to use the term) post-Marxist reading of his White Mythology: Metaphor in the Text of Philosophy. I am of the opinion that Derrida's works lend themselves superbly to politically motivated readings, and I also think that in undertaking such a reading I am opposing a dangerous mainstream approach to deconstruction, one which is virtually devoid of any political, cultural, or social interest or reference. My thesis is thus an attempt to read politically or economic:ally a theory of metaphor which is far more explicitly economic and political than academic consensus allows.
Keywords: words, world, Marxist cultural theories, atavism, relative sameness, deconstructive theorists